Double stranded scission of DNA directed through sequence-specific R-loop formation. - Landgraf, R (1995)
R-loop formation with short (100 nt) RNAs provides a highly flexible and stringent method to achieve sequence-specific separation of target DNA at any given sequence. After stabilization of R-loops with glyoxal and removal of the RNA through RNase treatment the remaining single-stranded DNA bubble provides a highly favorable substrate for attenuated micrococcal nuclease. We investigated this method for sequence-specific scission of double-stranded DNA and achieved quantitative scission of 3-5 kb plasmids. The applicability to larger size DNA is demonstrated through specific excision of the intervening segment between two R-loops from a P1 plasmid of approximately 120 kb.